Performance Characterization of Stone Mastic Asphalt using Steel Fiber - Shaffie, Ekarizan; Rashid, H.A.; Shiong, Fiona; Arshad, Ahmad Kamil; Ahmad, Juraidah; Hashim, Wardati; Putra Jaya, Ramadhansyah; Masri, Khairil Azman (Journal of Advanced Industrial Technology and Application, 2021)
SMA is a gap-graded hot mixture designed to provide higher resistance towards permanent deformation and rutting potential by 30% to 40% more than dense-graded asphalt, due to its stable aggregate skeleton structure. However, compared to other types of hot mix asphalt, SMA unfortunately has some shortcomings in term of its susceptibility towards moisture-induced damage due to its structure and excessive bitumen content in the composition. This research aims to assess the performance of a SMA mixture with steel fiber by enhancing overall stability, abrasion resistance, and, most importantly, moisture susceptibility. This study involved the incorporation of various steel fibre proportions of 0%, 0.3%, 0.5% and 0.7% by the total weight of mixture. The steel fibre modified SMA was made up of 6.0% PEN 60/70 bitumen content. The performance of SMA were evaluated through Marshall stability and flow test, Cantabro loss test and indirect tensile strength test. The results obtained from the testing showed that the incorporation of steel fibre is significantly effective to enhance the resistance towards moisture damage, while increasing the stability and reducing the abrasion loss of SMA mixture, compared to conventional mixture. Overall, it can be concluded that the addition of steel fibre in asphalt mixture specifically SMA, has improved the mechanical performance in the application of asphalt pavement with the optimum steel fibre proportion of 0.3% by the weight of mixture. The developed models between the independent variables and responses demonstrated high levels of correlation. The study found that response surface methodology (RSM) is an effective statistical method for providing an appropriate empirical model for relating parameters and predicting the optimum performance of an asphaltic mixture to reduce flexible pavement failure.